Improving Children’s Ability in Knowing Vocabulary through the Experiential Learning Model Approach - Rini, Ratu Yustika; Indah, Opik Dwi (Jurnal Dieksis ID, 2023)
Developing the vocabulary comprehension skills require a complete understanding to be obtained by the children. This study aims to improve the children’s ability recognize vocabulary through the Experiential Learning Approach for children aged 4-5 years in group A of Ulil Albab Kindergarten. This research used group action research method. The subjects of this study were 12 people. The method of data collection in this study used observation, interviews, and documentation while the data analysis technique used mix method. The results of this study indicate that there is an increase of ability to recognize the concept of numbers for children, in the pre cycle there is 49.7%. Experiencing an increase in cycle 1 of action 1 of 61.1% and increased again in cycle 2 of action 2 of 91.1%. It is concluded that the Experiential Learning approach was very low possibility applied to improve children's skills in writing numbers and connecting vocabulary symbols with objects, because there is no significant change in its application. The Experiential Learning approach is very suitable to be applied in object comparisons. As for recommendations for teachers: the Experiential Learning approach can be used as an alternative approach in improving the ability to recognize vocabulary for children in group A of Ulil Albab Kindergarten. The findings in this study are that the use of the Experiential Learning approach is still not fully experienced directly because it adapts to the achievement indicator which still has to use paper pencil. But, so far the approach taken is appropriate because it doesn't really change the pattern of learning that has been done in Kindergarten which is more to the direct learning.